American torture : from the Cold War to Abu Ghraib and beyond - Otterman, Michael (Pluto Press, 2007)
-- Exposes the secret history of US torture at home and abroad --George W. Bush calls them an alternative set of procedures, vital tools needed to protect the American people and our allies. These tools include forced standing for up to forty hours, sleep deprivation for weeks on end, dousing naked prisoners with ice water in rooms chilled to ten degrees, and strapping prisoners to inclined boards then flooding their mouths with water. These techniques are torture, and they are used by the United States of America. American Torture reveals how torture became standard practice in todays War on Terror. Long before Abu Ghraib became a household name, the US military and CIA used torture with impunity at home and abroad. Billions of dollars were spent during the Cold War studying, refining, then teaching these techniques to American interrogators and to foreign officers charged with keeping Communism at bay. As the Cold War ended, these tortures were legalised using the very laws designed to eradicate their use. After 9/11, they were revived again for use on enemy combatants detained in Americas vast gulag of prisons across the globe, from secret CIA black sites in Thailand to the detention centre at GuantÁnamo Bay, Cuba. American Torture shows that the road to Abu Ghraib leads back through US military survival schools, Latin American military assistance programs, Vietnamese counter-terror operations and, finally, to Americas Cold War enemies: the USSR and communist China. It traces how the practice was refined, spread and kept legal. Such methods violate more than international law and fundamental human rights. As Michael Otterman reveals, they radicalise enemies, undermine credibility and yield unreliable intelligence. Above all, they do not make us more safe.